Pemberdayaan Masyarakat Dalam Penanggulangan Air Limbah Rumah Tangga Menjadi Pupuk Kompos Dengan Sistem Biopori Di Desa Jembatan Kembar Timur Kabupaten Lombok Barat - Hasyim; Rohani; Karyawan, I Dewa Made Alit; Negara, I Dewa Gede Jaya; Yasa, I Wayan; Saidah, Humairo; Mahendra, Made; Suteja, I Wayan; Salehudin; Sideman, IAO Suwati (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The legal age of marriage in Indonesia is a man and woman who have reached the age of 19 as stated in Law Number 16 of 2019 on the amendment of Law Number 1 of 1974 concerning marriage in Indonesia. Marriage under the age of 19 is called early marriage, which is known as the "Merariq Kodeq" tradition for the Sasak tribe in West Nusa Tenggara. The purpose of this research is to find out the ethnobiological perspective of the Merarik Kodeq culture in West Lombok and find out the efforts that have been made by the local government of West Lombok Regency to prevent the increasing prevalence of Merarik Kodeq West Lombok. This research uses descriptive qualitative methods. The informants involved in this study were selected using a purposive sampling technique based on predetermined criteria, namely couples who married at an early age. The results stated that the average age of early marriage in West Sekotong Village is 16-17 years old. At this age, the reproductive organs are still in the developmental stage, especially the female reproductive organs which will function as a place for the development of the fetus. So if a pregnancy occurs at this age, there will be a high risk of miscarriage, birth defects, and even death of the mother and baby. So that to address the increasing number of Merarik Kodeq or early marriages the local government formed a movement known as the Anti Merarik Kodeq Movement (GAMAK).